Impact of growth regulators on pollen sterility and ovular fertility insesame (Sesamum indicum L.) genotypes: IMPACT OF GROWTH REGULATORS ON POLLEN STERILITY AND OVULAR FERTILITY IN SESAME - RUKEIYA BEGUM; AMITAVA DUTTA (Journal of Oilseeds Research, 2026)
Sesame is one of the oldest indigenous oilseed crops and is known as the "queen of oilseeds." It is a short-day, indeterminate plant. Sesame oil is used for edible purposes as well as a base for Ayurvedic preparations. Since no stable male-sterile line is available in sesame for hybrid seed production, the present experiment was conducted during the pre-kharif seasons of 2022-23 and 2023-24 at Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal, to study the effects of a growth promoter and a growth retardant on male sterility and ovular fertility in different sesame genotypes. The experiment was laid out in a split-plot design with six main-plot treatments and eight sub-plot treatments, replicated three times, with a plot size of 4 m × 1.5 m. The main-plot treatments comprised six genotypes: V1 (Rama), V2 (Savitri), V3 (Suprava), V4 (Tilottama), V5 (Shubhra), and V6 (Smarak). The sub-plot treatments consisted of eight plant growth regulator treatments: T1 (GA₃ @ 100 ppm), T2 (GA₃ @ 200 ppm), T3 (GA₃ @ 300 ppm), T4 (2,4-D @ 10 ppm), T5 (2,4-D @ 25 ppm), T6 (2,4-D @ 50 ppm), T7 (2,4-D @ 100 ppm), and T8 (control; water spray). The results indicated that, among the treatments, the application of 2,4-D @ 100 ppm resulted in maximum pollen sterility in Savitri, followed by Shubhra and Smarak, whereas minimum pollen sterility was observed in Rama under GA3 @ 200 ppm. The application of GA3 @ 100 ppm resulted in the highest ovular fertility, with Smarak, followed by Suprava, recording the maximum fertility when the mean of the two years was considered. Therefore, it may be concluded that the application of 2,4-D @ 100 ppm can be used to induce more than 50% pollen sterility, while GA3 @ 100 ppm may be recommended for enhancing ovular fertility.